Numerical analysis of cavity-based control of base pressure variations at supersonic Mach numbers - Ridwan, R; Khan, Sher Afghan; Syed Mohamed Ali, Jaffar; Sapardi, Mohd Azan Mohammed; Aabid, Abdul (Tech Science Press, 2023)
In the present study, the base pressure variations induced by the presence of a cavity, known to strongly influence the behavior of supersonic projectiles, are investigated through the numerical solution of the balance equations for mass, momentum, and energy. An area ratio of four is considered and numerical simulations are carried out at Mach M = 1.2, 1.4, 1.6, and 1.8 assuming no cavity or cavity locations 0.5D, 1D, 1.5D, and 2D. The inlet pressure of the nozzle is considered a flow variable. The Taguchi method is also used, and the considered cases are then analyzed using a full factorial experimental design. The results show that the cavity effectively increases the base pressure for the conditions examined. For other nozzle pressure ratios, cavities do not lead to passive control due to the change in the reattachment length. The distribution of wall pressure reveals that, in general, a cavity used to implement passive control of the base pressure does not adversely influence the flow pattern in the domain.